2022
DOI: 10.1007/s00406-022-01455-z
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography reveals retinal thinning in schizophrenia spectrum disorders

Abstract: Background Schizophrenia spectrum disorders (SSDs) are presumed to be associated with retinal thinning. However, evidence is lacking as to whether these retinal alterations reflect a disease-specific process or are rather a consequence of comorbid diseases or concomitant microvascular impairment. Methods The study included 126 eyes of 65 patients with SSDs and 143 eyes of 72 healthy controls. We examined macula and optic disc measures by optical coherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…As mentioned above, so far only preliminary retinal data from the CDP cohort have been published (119) because the sample size is not large enough to obtain sound results for all the variables examined. Of note, similar to the data in the initial OCT paper (119), we plan to make published data available to enable open research exchange. However, the fact that no further preliminary findings have been published is a limitation of the current status of the CDP study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, so far only preliminary retinal data from the CDP cohort have been published (119) because the sample size is not large enough to obtain sound results for all the variables examined. Of note, similar to the data in the initial OCT paper (119), we plan to make published data available to enable open research exchange. However, the fact that no further preliminary findings have been published is a limitation of the current status of the CDP study.…”
Section: Discussionmentioning
confidence: 99%
“…As a preliminary finding from the CDP study, we recently published OCT findings in 65 patients with an SSD and 72 HC that provided evidence of thinner inner retinal layers and thinner total macular thickness in SSDs (119). These changes could not be explained by comorbidities such as hypertension, diabetes, or higher body mass index (BMI), all of which also affect retinal thickness and are enriched in patients with SSD.…”
Section: Relationship Of the Cdp Study To International Cohort Studiesmentioning
confidence: 98%
“…impairment, which severely negatively impacts the overall functioning of the patient and hinders the recovery process [12]. As the three main characteristics of schizophrenia, positive symptoms, negative symptoms and cognitive deficits are closely correlated [13]. Studies have shown that the severity of negative and cognitive symptoms is associated with impairments in semantic memory, verbal memory and executive functioning, whereas positive symptoms are associated with semantic memory [14].…”
Section: Of 11mentioning
confidence: 99%
“…1 Recent studies using optical coherence tomography have provided evidence of retinal thinning in individuals with schizophrenia, suggesting that illness pathophysiology may be detected in the most distal and hence readily accessible part of the central nervous system. [2][3][4][5][6][7][8] These studies have shown inner retinal atrophy, thinning of peripapillary retinal nerve fiber layers and macular ganglion cell and inner plexiform layers, as well as an enlarged cup-disc ratio. This was also confirmed in a large and well-characterized cohort, 9 where individuals with schizophrenia showed an enlargement in cup disc ratio and a decrease in inner retinal thickness compared to healthy controls, beyond what could be attributed to the presence of hypertension and diabetes.…”
Section: Introductionmentioning
confidence: 97%